2017
DOI: 10.1080/1828051x.2017.1415705
|View full text |Cite
|
Sign up to set email alerts
|

Ewes giving birth to female lambs produce more milk than ewes giving birth to male lambs

Abstract: A total number of 23,271 parturitions were studied from two sheep farms of the Churra (CH) and Lacaune (LA) breeds. CH lambs were kept with their mothers during the first 30 days of age; from that moment onwards, ewes were machine-milked. LA lambs were not allowed to suckle their mothers, and ewes were machine-milked from parturition. Milking length (ML), total milk yield (TMY) and daily milk yield (DMY) (TMY/ML) were calculated. For the CH breed, there was an effect (p < .001) of prolificacy on ML, TMY and DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
6
14
0
Order By: Relevance
“…Rivasa et al [2] found similar results to this study, where the effect of parity number had significant differences (p < 0.01), with sheep from the second to the seventh parity showing the highest milk yields with respect to those sheep that recorded births past the eighth parity. Similarly, Rovai et al [18] also observed that the first parity corresponded with the lowest yields (p < 0.01), as well as in other studies conducted in Spain [23,24].…”
Section: Effect Of Parity Number Litter Size and Season Of Lambingsupporting
confidence: 58%
See 2 more Smart Citations
“…Rivasa et al [2] found similar results to this study, where the effect of parity number had significant differences (p < 0.01), with sheep from the second to the seventh parity showing the highest milk yields with respect to those sheep that recorded births past the eighth parity. Similarly, Rovai et al [18] also observed that the first parity corresponded with the lowest yields (p < 0.01), as well as in other studies conducted in Spain [23,24].…”
Section: Effect Of Parity Number Litter Size and Season Of Lambingsupporting
confidence: 58%
“…Prolificacy positively influences dairy milk production, being higher in those sheep that gestated two or more lambs as compared with sheep that only birthed one lamb [16,24] (Figure 3). This difference is determined by the total volume of the placenta and an increased production of placental hormones (galactono-placental) that influence the development of the mammary structure before birth.…”
Section: Effect Of Parity Number Litter Size and Season Of Lambingmentioning
confidence: 99%
See 1 more Smart Citation
“…While trying to explain a significant effect of parity on dairy yield traits, authors usually emphasise increased development of rumen in later lactations which is usually directly accompanied with higher food intake and consequently higher milk production. The results pertaining to the effect of litter size are in line with numerous reports on this issue (Snowder and Glimp, 1991;Hassan, 1995;Özder et al, 2004;Pollott and Gootwine, 2004;Fuerst-Waltl et al, 2005;Reiad et al, 2010;Sezenler et al, 2016;Abecia and Palacios, 2017).…”
Section: Resultssupporting
confidence: 86%
“…The SNPs associated with the MY trait are located in OAR2_65914681.1 (Chr 2: 61,498,071 bp), OAR18_22964031.1 (Chr 18: 22,346,018 bp), OAR20_5129052.1 (Chr 20: 5,085,823 bp), OAR20_11623776.1 (Chr 20: 11,249,238 bp), and OAR20_31210307.1 (Chr 20: 28,418,356 bp). In Churra sheep and Lacaune breeds, ewes presenting twin parturitions produced more milk than ewes with single parturitions, and the presence of female lambs had a positive effect on milk yield [60]. In sheep, litter size has a positive correlation with the incidence of breastfeeding and milk production [61].…”
Section: Markers Associated With Prolificacy Traitsmentioning
confidence: 99%